Customers loyalty towards Kompleks Tabung Haji Kota Kinabalu / Zurina Ismail - Ismail, Zurina (2006)
This research is a study on customers' loyalty towards Kompleks Tabung Haji Kota Kinabalu (KTHKK).The objective of this research is to evaluate the customer satisfaction level on services and facilities provided by the KTHKK and also to determine the willingness of the visitors to be loyal with the KTHKK. There are ten major elements that used in this research to determine the level of satisfaction towards KTHKK such as room services, staff performance, guest room, facilities, restaurant, lobby, cleanliness, timeliness and ambiance and atmosphere. Loyalty of a firm's customer has been recognized as the dominant factor in a business organization's success. Customers' loyalty towards KTHKK was measured by 3 items such as their willingness to return, their positive word of mouth intention and their willingness to not switch to other brands. Using data collected from Kompleks Tabung Haji Kota Kinabalu indicate that most of visitors were satisfied with the room services, staff performance, guest room, facilities, restaurant, lobby, time taken in providing service, cleanliness, ambience and atmosphere. Furthermore, the findings also imply that visitors were willing to be loyal with the KTHKK.